Market Efficiency and Natural Selection in a Commodity Futures Market - Luo, Guo Ying (Review of Financial Studies, 1998)
While the literature usually justifies informational efficiency in the context of rationality, this article shows informational efficiency by applying the evolutionary idea of natural selection. In a dynamic futures market, speculators are assumed to merely act upon their predetermined trading types (buyer or seller), their predetermined fractions of wealth allocated for speculation, and their inherent abilities to predict the spot price, reflected in their distributions of prediction errors with respect to the spot price. This article shows that the proportion of time that the futures price equals the spot price converges to one with probability 1.